Design and Implementation of Operating System Components and Data Acquisition for the 300 keV/20 mA EBM at PSTA-BATAN Yogyakarta - Ramadhani, Ahmad; Budianto, Anwar; Franata, Nauval; Ali Setyo Yudono, Muchtar; Verlaili Erlindriyani, Ratu (Devotion : Journal of Research and Community Service, 2025)
The development of operating system components and a data acquisition system for the 300 keV/20 mA Electron Beam Machine (EBM) at PSTA-BATAN Yogyakarta has been conducted. The system is designed to control and monitor key operational parameters, including input oscillator power voltage, high voltage, beam current, electron gun voltage, and vacuum pressure. It integrates hardware consisting of the PLC FX2424 module, L-Relay 51, and regulated power supply with software developed using LabVIEW 2018 and i-TRiLOGI 7.01. The development process involved programming the operating system in i-TRiLOGI , establishing PLC–LabVIEW communication, and implementing monitoring and data acquisition features in LabVIEW. The system enables remote operation of EBM components via a computer interface and provides real-time visualization of parameters in graphical and tabular formats. Data storage and export functions are also included to support further analysis. Testing results indicate that PLC–LabVIEW communication operates reliably via serial protocol, while ADC testing of the PLC produced a linear response with a correlation value of 1. Data presentation in LabVIEW HMI was accurate and could be exported into Microsoft Excel and Word, confirming the system's functionality for both operation and data acquisition